PENGARUH KETIDAKPASTIAN LINGKUNGAN TERHADAP KINERJA MANAJEMEN PADA PT DIRGANTARA INDONESIA - Paryati, Retno (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2022)
This research includes analytical descriptive research using case study techniques, with the aim of knowing how the influence of environmental uncertainty on managerial performance in empirical studies at PT Dirgantara Indonesia. This study uses primary data from PT Dirgantara Indonesia with a population of 50. The sampling method uses the census method. The data processing technique uses simple linear regression analysis using SPSS software version 27. The results of the analysis show that the environmental uncertainty variable has an effect on managerial performance. And environmental uncertainty has an influence of 55.5% on management performance. While the remaining 44.5% is the influence of other factors outside of environmental uncertainty that were not observed in this study.